2020
DOI: 10.1111/bjh.16956
|View full text |Cite
|
Sign up to set email alerts
|

Haematological cancers and the risk of severe COVID‐19: Exploration and critical evaluation of the evidence to date

Abstract: Summary From the outset of the COVID‐19 pandemic, patients and healthcare professionals have been concerned that a history of haematological malignancy will lead to an increased risk of severe COVID‐19. This led to the UK government advising patients with blood cancers to shield, massive re‐organisation of NHS haematology and cancer services, and changes in treatment plans for thousands of patients. Given the unknown effects that relaxation of social‐distancing measures will have on the infection rate, we revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 38 publications
(125 reference statements)
2
25
0
Order By: Relevance
“…21 There are several reasons why haematological cancer patients could be more susceptible to severe outcomes, namely the negative impact of the cancer itself or its treatment on the immune system. 22 There is utility in making this comparison in a study such as ours where all individuals are on active treatment, as it removes the potential confounding of patients off-treatment shielding at home more strictly. The most recent UKCCMP study by Lee et al found a higher prevalence of COVID-19 in haematological patients 10 ; a reason for the discrepancy in our data could be due to the heterogeneous group that leukaemia encompassed and the overrepresentation of myelodysplastic syndromes in our cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 There are several reasons why haematological cancer patients could be more susceptible to severe outcomes, namely the negative impact of the cancer itself or its treatment on the immune system. 22 There is utility in making this comparison in a study such as ours where all individuals are on active treatment, as it removes the potential confounding of patients off-treatment shielding at home more strictly. The most recent UKCCMP study by Lee et al found a higher prevalence of COVID-19 in haematological patients 10 ; a reason for the discrepancy in our data could be due to the heterogeneous group that leukaemia encompassed and the overrepresentation of myelodysplastic syndromes in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“… 21 There are several reasons why haematological cancer patients could be more susceptible to severe outcomes, namely the negative impact of the cancer itself or its treatment on the immune system. 22 There is utility in making this comparison in a study such as ours where all individuals are on active treatment, as it removes the potential confounding of patients off-treatment shielding at home more strictly. The most recent UKCCMP study by Lee et al .…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary reports suggest that patients with an underlying malignancy have inferior outcomes. [3][4][5][6][7] While haematology patients are thought to be at increased risk of developing severe complications both due to immune dysfunction from their underlying haematological disorder and immunosuppressive therapies used for treatment, [8][9][10] delays in treatment of the underling malignancy may compromise patient safety and survival. Data from other cohorts worldwide suggest mortality from COVID-19 is higher in haematology patients compared to the general population, 3,11,12 with reported mortality rates between 39% and 50% in other British haematology patient cohorts.…”
mentioning
confidence: 99%
“…Following the onset of the COVID‐19 pandemic in early 2020, a range of risk factors have been identified underpinning the severity of infection observed in some patients following SARS‐CoV‐2 infection 1 . These include obesity, advancing age, co‐morbidities such as diabetes, hypertension and cardiovascular disease and more recent publications have also reported a significantly increased mortality in patients with underlying haematological malignancy 2 . A greater risk may be anticipated in stem cell transplant recipients due to significant additional treatment‐related immunosuppression although the magnitude of the additional risk from the transplant procedure versus that from the underlying diagnosis and patient‐related factors is uncertain 3 .…”
Section: Number Of Centres Providing Data Routine Testing Testing Stamentioning
confidence: 99%
“…1 These include obesity, advancing age, co-morbidities such as diabetes, hypertension and cardiovascular disease and more recent publications have also reported a significantly increased mortality in patients with underlying haematological malignancy. 2 A greater risk may be anticipated in stem cell transplant recipients due to significant additional treatment-related immunosuppression although the magnitude of the additional risk from the transplant procedure versus that from the underlying diagnosis and patient-related factors is uncertain. 3 A recent prospective study of the outcome for 272 HSCT recipients that tested positive for SARS-CoV-2 in European transplant centres reported a mortality rate of 30% and 25Á3% for allogeneic and autologous HSCT recipients respectively, 4 emphasising the high mortality risk to HSCT recipients from this virus.…”
mentioning
confidence: 99%